Pelatihan Team Building untuk Meningkatkan Kepercayaan Antar Pribadi Serta Mutu Kerjasama di PT.RP - Mulia Sari, Indah; Soebandono, JP (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2023)
This research aims to design intervention team building training to improve interpersonal trust and teamwork quality. In addition to determine the effect of interpersonal trust to the teamwork quality at RP Company. Measuring instrument used is a measure of adaptation teamwork quality (Hoegl & Geumenden, 2001) and the interpersonal trust questionnaire (McAllister, 1995), by the number of study participants as many as 43 employees from 124 employees as population. The results of calculations using multiple regression showed R² = .783 (p<0,05) which means interpersonal trust in affects the Kerjasama quality at 78,3%. The t-test values obtained for the dimension of interpersonal trust is 6.085 (p<0,05) for cognition based trust and 3.163 (p<0,05) for affect based trust. Therefore, team building training made in the study was designed to increase interpersonal trust and teamwork quality.